2015
DOI: 10.3109/13697137.2014.996124
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis impacts quality of life in postmenopausal women

Abstract: This study has identified that postmenopausal women with chronic periodontitis report significantly poorer quality of life than healthy patients. Clinicians caring for postmenopausal women should be aware that periodontitis also impacts quality of life when making referral decisions for oral health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…It is therefore likely that female smokers with T2DM in the postmenopausal phase may exhibit variation in the expression of periodontal disease activity compared with male smokers with T2DM. 34 Furthermore, in the present study, controls were smoking almost twice as many cigarettes (15 cigarettes daily) compared with patients with T2DM (6 cigarettes daily). It is tempting to hypothesize that smokers with T2DM who smoke 15 cigarettes a day may exhibit more intense periodontal inflammation compared with never-smokers with T2DM.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…It is therefore likely that female smokers with T2DM in the postmenopausal phase may exhibit variation in the expression of periodontal disease activity compared with male smokers with T2DM. 34 Furthermore, in the present study, controls were smoking almost twice as many cigarettes (15 cigarettes daily) compared with patients with T2DM (6 cigarettes daily). It is tempting to hypothesize that smokers with T2DM who smoke 15 cigarettes a day may exhibit more intense periodontal inflammation compared with never-smokers with T2DM.…”
Section: Discussionmentioning
confidence: 46%
“…It is known that hormonal changes and the postmenopausal state influence periodontal health status. It is therefore likely that female smokers with T2DM in the postmenopausal phase may exhibit variation in the expression of periodontal disease activity compared with male smokers with T2DM 34 . Furthermore, in the present study, controls were smoking almost twice as many cigarettes (≈15 cigarettes daily) compared with patients with T2DM (≈6 cigarettes daily).…”
Section: Discussionmentioning
confidence: 56%
“…It is known that hormonal changes and postmenopausal state influences periodontal health status. It is therefore likely that WS females with T2DM and in the postmenopausal phase may exhibit variation in the expression of peri‐implant inflammatory parameters as compared to males . Another limitation is that the individuals had poorly‐controlled T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore likely that WS females with T2DM and in the postmenopausal phase may exhibit variation in the expression of peri-implant inflammatory parameters as compared to males. 35 Another limitation is that the individuals had poorly-controlled T2DM. It has been reported that dental implants can osseointegrate and remain functionally stable among patients with well-controlled diabetes in a manner similar to non-diabetic individuals.…”
Section: Peri-implant Parameters All Individuals Waterpipe Smokers Nementioning
confidence: 99%
“…Reports suggest that even in the absence of acute presentation, the dental condition impacts QoL as a more complex interaction; chronic conditions and esthetic complaints deviate from the norm establishing a "new normal" which is a QoL compromise. [13][14][15] Similarly, dental interventions involving implants to replace lost teeth improve QoL. 16 Dental studies on oral disease management commonly examine the subject on the basis of pathogenesis, risk factors, treatment efficacy and outcome.…”
Section: Introductionmentioning
confidence: 99%